학령기 남녀 아동의 일상적 생활 스트레스에 미치는 내현적 자기애적 성향과 자기통제의 영향 - 민하영; Min, Ha Young (Korean Journal of child studies, 2013)
The purpose of this study was to investigate the influence of covert narcissism and self control on the daily stresses encountered by school-age boys and girls. The subjects were 517 children who attended in elementary schools in Daegu and Gyeongbuk Province. Self reporting questionnaires were used to investigate covert narcissism, self control and daily stresses. The data thus collected were analyzed by means of Pearson's correlation, multiple regression, using SPSS Win 19.0. The results are as follows. (1) In term of daily stresses, the regression findings indicated the main effect of covert narcissism and self control. Daily stresses increased as school-age boys' and girls' covert narcissism increased or their self control decreased. (2) Covert narcissism influenced more on daily stresses than self control did for both boys and girls. (3) There were significant interactions between school-age girls' covert narcissism and self control in term of daily stresses.